Infusing Inuit and local knowledge into the Low Impact Shipping Corridors: An adaptation to increased shipping activity and climate change in Arctic Canada. Issue 105 (March 2020) - Dawson, Jackie; Carter, Natalie; van Luijk, Nicolien; Parker, Colleen; Weber, Melissa; Cook, Alison; Grey, Kayla; Provencher, Jennifer
Highlights: Climate change and sea ice reduction have influenced an increase in Arctic ship traffic. Climate change and increased Arctic shipping are impacting Inuit livelihoods. Low impact shipping corridors need to consider culturally significant marine areas. Communities recommend changes to the low impact shipping corridors in Arctic Canada. Findings reiterate the need for inclusion of northern voices in Arctic shipping policy. Abstract: Ship traffic has nearly tripled in the Canadian Arctic over the past decade and additional growth is expected as climate change continues to increase navigability in the region. In response, the Canadian Government is developing Low Impact Shipping Corridors as an adaptation strategy that supports safety and sustainability under rapidly changing environmental conditions. The corridors are voluntary maritime routes where services and infrastructure investments are prioritized. While a large amount of data from different sources were used to establish the location of the corridors, important local and Indigenous knowledge from Arctic communities has yet to be considered in much detail. The Arctic Corridors and Northern Voices (ACNV) project was established in response to this fundamental gap in knowledge. The purpose of this paper is to outline perspectives and recommendations for the corridors from 13 Canadian Arctic communities across Inuit Nunangat (Inuit homeland) that were involved in the ACNV project through a series of participatory community mapping workshops. A summary of the recommendations for the corridors that emerged from communities is presented including spatial representations for: 1) preferred corridors, 2) areas to avoid, 3) restrictions by season, 4) modification of vessel operation and 5) areas where charting is needed. The findings of the study further reiterate the vital need for meaningful inclusion of northern voices in the development of Arctic shipping policy and governance.